Effective Use of ICT in Enhancing Classroom Learning Experiences - Angkur, Maria Fatima Mardina; Khan, Razia; Zaman, Khalil; Walid, Abul (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
The integration of Information and Communication Technology (ICT) in education has gained significant attention for its potential to transform traditional classroom learning. ICT tools offer new ways to enhance student engagement, provide access to diverse resources, and foster interactive learning environments. However, the effective use of ICT in the classroom requires a strategic approach to ensure that technology serves as a facilitator of learning rather than a distraction. This research aims to investigate how the effective use of ICT can enhance classroom learning experiences by examining its impact on student engagement, collaboration, and academic outcomes. A mixed-methods research design was employed, combining quantitative surveys and qualitative interviews. Data were collected from 150 students and 30 educators across various educational levels, focusing on the types of ICT tools used, the frequency of use, and the perceived impact on learning. The survey data were analyzed statistically, while the interviews provided deeper insights into the experiences and challenges associated with ICT integration. The findings indicate that the strategic use of ICT in the classroom significantly enhances student engagement and collaboration. Students who used ICT tools frequently reported higher levels of motivation and participation in class activities. However, the study also identified challenges such as inadequate teacher training and technological issues, which can hinder the effectiveness of ICT. In conclusion, the research suggests that when used effectively, ICT can greatly improve classroom learning experiences by fostering engagement and interactivity. The study highlights the need for ongoing teacher training and technical support to maximize the benefits of ICT in education.